The lifeways of small-scale gold miners: Addressing sustainability transformations - Fisher, Eleanor; Theije, Marjo de; Araujo, Carlos H.X.; Calvimontes, Jorge; Camp, Esther van de; D’Angelo, Lorenzo; Lanzano, Cristiano; Luning, Sabine; Massaro, Luciana; Mello, Januaria; Ouedraogo, Alizeta; Pijpers, Robert J.; et al. (Global Environmental Change, 2023)
Small-scale gold mining sustains millions of people’s lives and yet it stimulates environmental harms and social conflicts. Global environmental crises drive calls for fundamental change to how people live on the planet. For small-scale gold mining, this raises questions about whether current dynamics can provide a basis for sustainability transformations. Proposing the notion of gold lifeways to focus on the lived experience of mining and gold resources as relational phenomena, we ask what sustainability looks like from different miners’ perspectives and probe the practice dynamics of current transformation. Our methodology is social science-led and transdisciplinary. From multi-sited and trans-regional research between South America and Africa, we draw cases from Suriname, Guinea Conakry, and Uganda. Our study finds that gold lifeways give expression to different strands of sustainability: sustaining everyday life in mining; discourses framing mining practices; and government repression of mining. Hence, as our empirical data demonstrates, miner perspectives on sustainability gain content not in isolation, but as part of gold lifeways embedded within different contexts and shaped by societal dynamics. Ultimately, the transformative potency of small-scale gold mining is located in personal lives and precarious dynamics rather than glittering promises of a sustainable future.
Keywords: Small-scale gold mining; Gold lifeways; Materiality; Sustainability transformations; Transdisciplinary